CFD, energy, and exergy analysis and sustainability indicators of tilapia fish strips drying using an evacuated tubes indirect solar dryer - Amena Ali Alsakran; Omar Shahat Younis; András Székács; Omar Saeed; Mohamed Hamdy Eid; Ali Majrashi; Atef Fathy Ahmed; Aml Abubakr Tantawy; Abdallah Elshawadfy Elwakeel (Scientific Reports)
Abstract This study evaluates the performance of an evacuated tube indirect solar dryer (ETISD) for drying tilapia strips at three thicknesses (4, 8, and 12 mm) using computational fluid dynamics (CFD), energy-exergy analysis, and sustainability indicators. CFD simulations were employed to analyze airflow patterns, temperature distribution, and velocity profiles inside the drying room (DR) across five air velocities (0.02–0.06 m/s). The optimal air flow rate of 0.03 m3/s provided a uniform drying temperature of 74.82 °C, at solar noon. Simulations over two consecutive drying days (8 a.m.–5 p.m.) further assessed thermal and aerodynamic behavior, enhancing system optimization. Energy analysis revealed that the evacuated tube solar collector (ETSC) achieved a maximum input energy of 1311.8 W and useful energy of 682.5 W, with energy efficiencies of 44.5–51.2% (ETSC) and 16.18–21.57% (ETISD). Exergy efficiencies ranged from 8.51 to 21.99% (ETSC) and 29.23–84.76% (ETISD), highlighting thermodynamic performance. Sustainability indicators, including improvement potential (IP) (2.71–6.69 W), waste exergy ratio (WER) (1.15–1.36), and sustainability index (SI) (1.09–1.28), demonstrated the system’s environmental and operational viability. These findings underscore the ETISD’s effectiveness for sustainable tilapia drying, balancing energy efficiency, thermal performance, and ecological impact.